Pollyanna grows up - Porter, Eleanor H.; Taylor, Henry Weston (The Page Company, 1915)
As Pollyanna grows up she continues her philosophy of gladness, bringing happiness to all those around her.
At head of title: The second glad book ...
As Pollyanna grows up she continues her philosophy of gladness, bringing happiness to all those around her.
Keywords: Orphans / Juvenile fiction; Juvenile works / fast; Fiction / fast